1995
DOI: 10.1083/jcb.128.6.1029
|View full text |Cite
|
Sign up to set email alerts
|

Dual pathways of internalization of the cholecystokinin receptor.

Abstract: Abstract. Receptor molecules play a major role in the desensitization of agonist-stimulated cellular responses. For G protein-coupled receptors, rapid desensitization occurs via receptor phosphorylation, sequestration, and internalization, yet the cellular compartments in which these events occur and their interrelationships are unclear. In this work, we focus on the cholecystokinin (CCK) receptor, which has been well characterized with respect to phosphorylation. We have used novel fluorescent and electron-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
159
3
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(177 citation statements)
references
References 55 publications
13
159
3
1
Order By: Relevance
“…Hence, our finding that CB1R shows a lysosomal localization could represent fundamental basis to further studies about receptor internalization, downregulation and eventual resensitization which constitute essential steps to analyze receptors function and signalling within the cells. For several receptors, the cellular responses to effectors have been shown to be regulated in part by the compartmentalization of the receptors and their effectors within the cells [40], therefore elucidating the mechanism underlying the trafficking of CB1R is critical for understanding the physiological response to a variety of ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our finding that CB1R shows a lysosomal localization could represent fundamental basis to further studies about receptor internalization, downregulation and eventual resensitization which constitute essential steps to analyze receptors function and signalling within the cells. For several receptors, the cellular responses to effectors have been shown to be regulated in part by the compartmentalization of the receptors and their effectors within the cells [40], therefore elucidating the mechanism underlying the trafficking of CB1R is critical for understanding the physiological response to a variety of ligands.…”
Section: Discussionmentioning
confidence: 99%
“…With a signaling system having a soluble ligand that cannot cross the lipid bilayer and that is delivered from the extracellular milieu, any movement of the receptor off the cell surface functionally desensitizes it. Two such internalization pathways have been described for the CCK 1 receptor, clathrin-mediated endocytosis and potocytosis via caveolae (Roettger et al, 1995b). Similarly, coupling between receptor and G protein requires lateral mobility in the plasma membrane and access for the two molecules to meet each other (Roettger et al, 2001).…”
Section: Cellular Mechanisms Of Regulation Of Cck Receptorsmentioning
confidence: 99%
“…The group of G-proteincoupled receptors, whose main function is to transduce information from the extracellular environment to the interior of the cell, initiates this process after a specific ligand has been bound to its receptor, thereby facilitating transmembrane signalling. Both clathrin-coated pits (Ghinea et al 1992, Von Zastrow & Kobilka 1992, Hoxie et al 1993, Von Zastrow et al 1993, Roettger et al 1995 and uncoated endocytic pathways (Raposo et al 1989, Roettger et al 1995 have been suggested to be involved in the internalisation of G-protein-coupled receptors. Clathrin-coated pits require cytoplasmic receptor motifs in order to interact with proteins of the endocytic machinery (Trowbridge et al 1993, Clague 1998.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear whether both clathrin-coated pits and uncoated endocytic pathways play a similar role. The cholecystokinin receptor-ligand complex internalised by uncoated pits has been purported to mediate rapid resensitisation of the receptor (Roettger et al 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation